Implementation of The Merdeka Curriculum in Physics Learning at Senior High Schools in Bengkulu City - Rafikah Dalilah; Andik Purwanto; Iwan Setiawan (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in physics learning at high schools in Bengkulu City, focusing specifically on SMA Negeri 4, SMA Negeri 8, and SMA Negeri 9 Bengkulu City. Additionally, it examines students' responses to implementing the Merdeka Curriculum in physics learning at these three schools. The background of this research stems from the